2020
DOI: 10.3389/fvets.2019.00497
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Woody Breast Myopathy in a Meat Broiler Line by Heat Production, Microbiota, and Plasma Metabolites

Abstract: Selection for quantitative traits in meat broilers such as breast yield and growth rate exert physiological pressure leading to ante mortem histological and biochemical alterations in muscle tissues. The poultry industry has recently witnessed a myopathy condition affecting Pectoralis major (breast muscle) of broilers, called woody breast (WB), an etiology still unclear to scientific community. A study was conducted to characterize the WB myopathy in a meat broiler line at its finishing phase (d 41) in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 35 publications
(32 reference statements)
2
25
0
Order By: Relevance
“…Decreased protein synthesis and increased degradation is a physiological phenomenon that may contribute to muscle protein loss, whereas the proteolytic pathways (ubiquitin-proteasome, lysosomal, and calpain) may be more evident in enhanced degradation of muscle tissue ( Khalil et al., 2018 ; McCarthy and Murach, 2019 ; Maharjan et al., 2020b ). Furthermore, both strains had higher FDR values for myopathy-affected broilers than for nonmyopathy broilers, which was also validated by the relatively higher expression of 3-MH in plasma samples in myopathy-affected broilers for both strains ( Maharjan et al., 2020c ). Strain B had greater expression of 3-MH when compared between strains indicating higher mixed muscle degradation occurring than in strain A.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Decreased protein synthesis and increased degradation is a physiological phenomenon that may contribute to muscle protein loss, whereas the proteolytic pathways (ubiquitin-proteasome, lysosomal, and calpain) may be more evident in enhanced degradation of muscle tissue ( Khalil et al., 2018 ; McCarthy and Murach, 2019 ; Maharjan et al., 2020b ). Furthermore, both strains had higher FDR values for myopathy-affected broilers than for nonmyopathy broilers, which was also validated by the relatively higher expression of 3-MH in plasma samples in myopathy-affected broilers for both strains ( Maharjan et al., 2020c ). Strain B had greater expression of 3-MH when compared between strains indicating higher mixed muscle degradation occurring than in strain A.…”
Section: Discussionmentioning
confidence: 71%
“…3-MH Is considered a unique biomarker of myofibrillar protein breakdown, and its appearance level in blood or urine is indicative of the degree of breakdown occurring in muscle tissue ( Williamson et al., 1977 ; Tipton et al., 2018 ). Furthermore, Maharjan et al. (2020c) recently reported that myopathy-affected broilers had a differential expression of plasma metabolites that showed potential involvement of vascularity issues causing the poor arterial blood circulation in muscle tissue leading to localized hypoxia and increased muscle degradation and myodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On a histological level, WB myofibrils have degeneration with necrosis and accumulating fibrosis (interstitial connective tissue) and lipidosis [ 7 , 8 ]. From a biochemical perspective, WB fillets are found to be higher in fat, moisture, and collagen, and lower in protein and ash [ 9 , 10 ]. The physiological and biochemical changes in the meat lead to poor texture, lower water holding capacity (WHC), higher drip loss, and poor eating quality.…”
Section: Introductionmentioning
confidence: 99%